Hyperthermia study in breast cancer treatment using a new applicator (2019)
A study about effects obtained by implementing an electromagnetic hyperthermia (EM) treatment model are presented. The study focus is the breast cancer treatment; this study is perform using an electromagnetic simulation model. A breast was modeled using the conductivity and permittivity of tissues such as fat, skin, lobules and muscle. The distribution of the power density was analyzed for two cases, first the applicator is not aligned with the tumor; second the applicator is aligned with the applicator. The distribution of the power density was analyzed inside the breast model when it was irradiated with two applicators at 2.45 GHz and 5 GHz. The second applicator proposed it is a new prototype of applicator developed in the Groove Gap Waveguide technology (GGW). The power density obtained in lobes, tumor and fat is compared and it was observed that tissues overheating that are close to the tumor can be avoided by optimizing the applicator location. The preliminary results indicate that with the new prototype of applicator developed in the Groove Gap Waveguide technology (GGW) is possible to focus the EM energy. Moreover, the tissues close to the tumor obtain a lower concentration of power density.